Elastic Behavior of Nanophases in Polyvinyl Alcohol (PVA)/Bamboo Charcoal (BC) Nanocomposite Films - Mousa, Mohanad; Dong, Yu (Frontiers in Materials, 2018)
Polyvinyl alcohol (PVA) nanocomposite films reinforced with bamboo charcoal nanoparticles were successfully fabricated via solution casting and their nanomechanical properties in terms of material phases were determined by a peak force quantitative nanomechanical tapping mode (PFQNM). Our experimental results revealed that the elastic modulus of PVA semicrystalline phase in stack-bundle form was 24± 4.2 GPa with the semicrystalline phase width being 20-76 nm, as opposed to 11.4± 3.1 GPa and 18-65 nm for corresponding PVA amorphous phase accordingly. The incorporation of bamboo charcoal (BC) nanoparticles enhanced the elastic moduli of both crystalline and amorphous phases of PVA by ~51% and ~100%, respectively. Moreover, the phase width was decreased to be in range of 5-53 nm for crystalline phase and 4-35 nm for amorphous phase.